2007
DOI: 10.1007/s00520-007-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Specialized palliative care services are associated with improved short- and long-term caregiver outcomes

Abstract: Goals of work The goal of this study was to evaluate, at a population level, the association between specialized palliative care services (SPCS) and short- and long-term caregiver outcomes. Patients and methods The Health Omnibus Survey, a face-to-face survey conducted annually in South Australia since 1991, collects health-related data from a rigorously derived, representative sample of 4,400 households. This study included piloted questions in the 2001, 2002, and 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 66 publications
3
107
0
2
Order By: Relevance
“…An earlier randomized clinical trial by the same author showed improved quality of life and less depression in patients randomized to receive a nurse-led palliative care intervention within 8-12 weeks of a new diagnosis of advanced cancer 4 . Finally, a largescale survey extended those findings to show that early palliative care improved caregiver outcomes 5 .…”
Section: Early Referral To Palliative Care and Its Impactclinical Trimentioning
confidence: 75%
“…An earlier randomized clinical trial by the same author showed improved quality of life and less depression in patients randomized to receive a nurse-led palliative care intervention within 8-12 weeks of a new diagnosis of advanced cancer 4 . Finally, a largescale survey extended those findings to show that early palliative care improved caregiver outcomes 5 .…”
Section: Early Referral To Palliative Care and Its Impactclinical Trimentioning
confidence: 75%
“…Country areas with a population of 1,000 or more (based on Australian Bureau of Statistics (ABS) 1996 Census information) are included in proportion to the size of their population. This research group previously verified the content and construct validity supporting the use of this survey tool in palliative care service planning (8) and in assessing the impact of palliative care services on caregiver needs (9). While there is ongoing discussion on the definition or rural (10, 11), for the purposes of this analysis rural is defined as the postcode areas outside the Adelaide metropolitan area.…”
Section: Methodsmentioning
confidence: 83%
“…These concerns have also been reported by other patient groups. 12,21 Although there is conflicting evidence about the quality of care received in inpatient settings versus at home, 2 some patients perceive that having access to professional medical care in inpatient settings is essential. People may also feel a sense of security from receiving care at a hospital with which they are already familiar.…”
Section: Discussionmentioning
confidence: 99%